The World Heritage inscription: A symbol of international cooperation - Feng Jing; Susan Denyer (The UNESCO Courier, 2023)
As Nelson Mandela once said: “It always seems impossible until it is done!” During its 38th session in June 2014 in Doha, Qatar, the World Heritage Committee inscribed The Silk Roads: the Routes Network of Chang’an-Tianshan Corridor on the World Heritage List. The serial property extends some 5,000 kilometres and encompasses 33 component sites in three countries, China, Kazakhstan and Kyrgyzstan.